Cinema as a Trendsetter and Source of Historical Research in Fashion (ModaPalavra e-periódico, 2019)
Although it emerged in Europe in the late nineteenth century, it was in the United States that cinema had its greatest development and consolidated as a multidisciplinary production activity and its multiple styles and genres became the subject of several studies. The correct interpretation of the symbolic contents of the film project enables an understanding of the socioeconomic conditions of an era and then becomes an important source of historical research. This article proposes a classification of cinema costumes, bringing a new look to the understanding of films that reconstitute other epochs, thus broadening the classification created by Betton (1987). For this article, three films of the musical genre were analyzed, considering a line of research on the influence exerted by the cinema in the construction of tendencies of the young culture wherethe music constitutes a central vector. The films analyzed are: Amor, Sublime Amor (1961), The Saturday Night Fever (1977) and Hair (1978), classified in the categories of period reconstruction, contemporary costumes and free interpretation of the time, allowing a more objective identification of ties between the socioeconomic reality of each era and the cinema, interfering in the constitution of habits and customs of a social group.
Keywords: fashion; cinema; history